Efficient criteria for the stabilization of planar linear systems by hybrid feedback controls - Elena Litsyn; Marina Myasnikova; Yurii Nepomnyashchikh; Arcady Ponosov (Abstract and Applied Analysis)
We suggest some criteria for the stabilization of planar linear systems via linear hybrid feedback controls. The results are formulated in terms of the input matrices. For instance, this enables us to work out an algorithm which is directly suitable for a computer realization. At the same time, this algorithm helps to check easily if a given linear 2×2 system can be stabilized (a) by a linear ordinary feedback control or (b) by a linear hybrid feedback control.